Rhabdomyolysis from influenza b infection: A case report (Indian Journal of Case Reports, 2019)
Rhabdomyolysis is a syndrome characterized by muscle necrosis and the release of intracellular muscle constituents into the circulation. Here, we report the case of an 18-year-old male with cerebral palsy who was admitted to the hospital with symptoms of lower respiratory tract infection and with high-grade fever. His initial blood workup revealed an elevated creatinine and CPK of 32,000 which was suggestive of rhabdomyolysis. His worsening renal function with acidosis and hyperkalemia required initiation of hemodialysis. A respiratory viral PCR profile revealed Influenza B. He was re-started on Oseltamivir with gradual clinical improvement. Respiratory viral PCR testing should be considered in patients with features of lower respiratory tract infection and rhabdomyolysis as this can detect influenza B and other viruses which cannot be detected by doing H1N1 PCR.